Дослідження режимів роботи фрагменту електричної мережі ПрАТ «Львівобленерго» з новою підстанцією «Чижиків» - Рак, Юрій Миколайович; Rak, Yurii Mykolaiovych (Національний університет "Львівська політехніка", 2024)
У ПрАТ «Львівобленерго» останнім часом відчувається дефіцит потужності і це є відчутною проблемою, для вирішення якої необхідний розвиток електричних мереж 110 кВ [1]. Розробка проекту розвитку електричної мережі вимагає вирішення ряду необхідних задач: реконструкції діючих підстанцій, їх розподільних злагод; реконструкції діючих ліній електропересилання; проектування нових підстанцій і ліній електричних мереж; дослідження режимів схеми розвитку електричної мережі. Об’єктом дослідження є фрагмент діючої ЕМ 110 кВ ПрАТ «Львівобленерго» з новозбудованою підстанцією «Чижиків» і повітряних ліній «Львів-2 – Винники», «Винники – Чижиків», «Чижиків – Куровичі НПС» та «Куровичі НПС – Красне». Предметом дослідження є схема розвитку фрагмента електричної мережі з врахуванням спорудження підстанції «Чижиків» та аналіз її усталених режимів. Мета роботи – розробити схему розвитку фрагмента нормальної схеми електричних з’єднань 110 кВ ПрАТ «Львівобленерго» з новозбудованою підстанцією «Чижиків», здійснити вибір нових трансформаторів підстанції «Чижиків», вибрати проводи повітряних ліній електропересилання та виконати аналіз режимів нової електричної мережі, вибрати її основне силове електроустаткування. Схему розвитку фрагмента електричної мережі з реконструйованою ПС «Чижиків» розроблено з врахуванням географічного розташування ПС «Чижиків» [2], карти-схеми ПЛ-110 кВ ПрАТ «Львівобленерго» [3], вимог чинних нормативних документів [4,5]. ПС «Чижиків» буде живитися від шин 110 кВ ПС «Винники» ПЛ-1 «Львів-2 – Чижиків» а у аварійному режимі від ПЛ-4 «Куровичі НПС – Чижиків». З дотриманням діючих правил і методик [5,6] вибрано головну схему електричних з’єднань ПС «Чижиків» та її основне силове електрообладнання. На цифровій моделі схеми розвитку фрагмента електричної мережі з ПС «Чижиків», яку сформовано у графічно-розрахунковому комплексі ДАКАР ЕЛЕКС [7], досліджено нормальні та післяаварійні усталені режими за максимального навантаження підстанцій «Винники» та «Куровичі НПС» з врахуванням спорудження ПС «Чижиків». Втрати активної потужності в електричній мережі з новозбудованою ПС «Чижиків» з живленням електричної мережі від шин 110 кВ ПС «Львів-2» становлять 1611 кВт при навантаженні мережі 61,775 + j31,712 МВА. За вимкнення трансформатора Т2 ПС «Чижиків» – 9938 кВт, за аварійного живлення від ПС «Куровичі НПС» – 1709 кВт. Схема розвитку електричної мережі з новозбудованою ПС «Чижиків» з живленням ПС «Львів-2» є оптимальною. Проводи діючих повітряних ліній «Львів-2 – Винники», «Винники – Чижиків», «Чижиків – Куровичі НПС» та «Куровичі НПС – Красне» у післяаварійних режимах мережі не перевантажувалися. Отже, заміну проводів діючих ПЛ на проводи більшого перерізу виконувати не потрібно. Розроблена схема розвитку електричної мережі ПрАТ «Львівобленерго» з новозбудованою ПС «Чижиків» може бути реалізована, так як ПЛ-110 кВ «Львів-2 – Винники», «Винники – Чижиків», «Чижиків – Куровичі НПС», а також «Куровичі НПС – Красне» за результатами дослідження нормальних, післяаварійних усталених режимів ЕМ і режиму перспективного навантаження, мають достатній запас по пропускній здатності. Рівень напруг на шинах 10 і 35 кВ підстанцій «Чижиків», «Винники» та «Куровичі НПС» буде забезпечений пристроями регулювання РПН і ПБЗ трансформаторів.

PrJSC "Lvivoblenergo" has recently experienced a power shortage and this is a tangible problem, for the solution of which the development of 110 kV electrical networks is necessary [1]. The development of a project for the development of an electrical network requires the solution of a number of necessary tasks: reconstruction of existing substations, their distribution networks; reconstruction of existing power transmission lines; design of new substations and electrical network lines; study of the modes of the electrical network development scheme. The object of the study is a fragment of the operating 110 kV power transmission line of PrJSC "Lvivoblenergo" with the newly built substation "Chyzhykiv" and the overhead lines "Lviv-2 - Vynnyky", "Vynnyky - Chyzhykiv", "Chyzhykiv - Kurovychi NPS" and "Kurovychi NPS - Krasne". The subject of the study is the development scheme of a fragment of the electric network taking into account the construction of the substation "Chyzhykiv" and the analysis of its steady-state modes. The purpose of the work is to develop a development scheme of a fragment of the normal scheme of electrical connections of PrJSC "Lvivoblenergo" with the newly built substation "Chyzhykiv", to select new transformers for the substation "Chyzhykiv", to select overhead power transmission line wires and to analyze the modes of the new electric network, to select its main power electrical equipment. The scheme of development of the fragment of the electric network with the reconstructed substation "Chyzhykiv" was developed taking into account the geographical location of the substation "Chyzhykiv" [2], the maps-schemes of the 110 kV overhead line of PrJSC "Lvivoblenergo" [3], the requirements of current regulatory documents [4,5]. The substation "Chyzhykiv" will be powered by the 110 kV buses of the substation "Vynnyki" of the 110 kV overhead line "Lviv-2 - Chyzhykiv" and in emergency mode from the 4th overhead line "Kurovychi NPS - Chyzhykiv". In compliance with the current rules and methods [5,6], the main scheme of electrical connections of the substation "Chyzhykiv" and its main power electrical equipment was selected. On the digital model of the development scheme of the electric network fragment with the “Chizhykiv” substation, which was formed in the graphic and computational complex DAKAR ELEKS [7], normal and post-accident steady-state modes at maximum load of the “Vynnyky” and “Kurovychi NPS” substations were studied, taking into account the construction of the “Chizhykiv” substation. Active power losses in the electric network with the newly built “Chizhykiv” substation with power supply from the 110 kV buses of the “Lviv-2” substation are 1611 kW at a network load of 61.775 + j31.712 MVA. When the transformer T2 of the “Chizhykiv” substation is turned off, it is 9938 kW, and when emergency power is supplied from the “Kurovychi NPS” substation, it is 1709 kW. The development scheme of the electric network with the newly built “Chizhykiv” substation with power supply from the “Lviv-2” substation is optimal. The wires of the operating overhead lines "Lviv-2 - Vynnyki", "Vynnyki - Chyzhykiv", "Chyzhykiv - Kurovichi NPS" and "Kurovichi NPS - Krasne" were not overloaded in the post-accident network modes. Therefore, it is not necessary to replace the wires of the operating overhead lines with wires of a larger cross-section. The developed scheme for the development of the electrical network of PrJSC "Lvivoblenergo" with the newly built substation "Chyzhykiv" can be implemented, since the 110 kV overhead lines "Lviv-2 - Vynnyki", "Vynnyki - Chyzhykiv", "Chyzhykiv - Kurovichi NPS", as well as "Kurovichi NPS - Krasne" according to the results of the study of normal, post-accident stable modes of the power system and the prospective load mode, have a sufficient margin of capacity. The voltage level on the 10 and 35 kV buses of the “Chyzhykiv”, “Vynnyky” and “Kurovychi NPS” substations will be provided with on-load tap-changer and PBZ transformer regulation devices.
Study of the operating conditions of the PrJSC «Lvivoblenergo» electric grid fragment with the new substation «Chyzhykiv»
Keywords: 6.141.00.00